Governança colaborativa: uma abordagem teórica, empírica e prática em parques tecnológicos - Abbud, Elenice Barcelar (2017)
The general objective of this dissertation organized in the form of two scientific articles and a technical article was to understand Collaborative Governance as a trend of public management, approaching it from the theoretical, empirical and practical perspectives. Following the UFLA Standardization Manual, which determines the standard for structured studies in the form of articles, in the first part, a general introduction was developed, with a brief contextualization of the problem was elaborated and presented the general and specific objectives. In the second part, three articles are presented that compose the three specific objectives of the scientific work. The first is a theoretical essay. Through it, we sought to discuss the implications of Collaborative Governance in current public administration practices. This initial effort served to identify fundamental theoretical elements of the Collaborative Governance, which was based on several authors who discuss the theme to answer what is the contribution of Collaborative Governance to the current public management. The second article filled the empirical perspective of Collaborative Governance analysis and was based on a study of the case. Through it, we proposed to analyze the strategic project of implantation of Science Parks in Minas Gerais conducted by the State Secretariat of Science, Technology and Higher Education (SECTES / MG), from the view of Collaborative Governance. We sought to interpret the study of the case from the theoretical assumptions developed in Article 1 and expressed in the relations interposed by the State with other actors of civil society, universities, and the market. To achieve this goal in a practical perspective of Collaborative Governance analysis and to provide a more applied contribution to the theme, the third article is of a technical nature and was developed through a Case of Teaching in Collaborative Governance of Science Parks. It is believed that this effort can be useful for teaching about the topics discussed throughout the theoretical and empirical studies. The result of this third article is a didactic-pedagogical material that can be used in undergraduate and postgraduate courses in Public Administration disciplines, with the objective of demonstrating the relevance of Collaborative Governance and providing the dissemination of the assumptions and characteristics of this contemporary approach of public administration. As a general result of the dissertation, the Collaborative Governance presents itself as a current trend of public management, making possible to understand of relations between the State, the market, and the society, in the formulation and implementation of public policies, connecting aspects of political nature with those of a techno-professional nature.